Anticipated tax reforms and temporary tax cuts: a general equilibrium analysis - Holger Strulik; Timo Trimborn (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2008)
Macroeconomic studies of tax policy in dynamic general equilibrium usually assume that reforms hit the economy unexpectedly and last forever. Here, we explore how previous results change when we allow policy changes to be pre-announced and of finite duration and when these facts are anticipated by households and firms. Quantitatively we demonstrate a headstart advantage from pre-announcement that is never caught up by a surprising reform. The welfare gain from announcement of a corporate tax cut, for example, is estimated to be around 10 percent of the total gain from the reform. We show that adjustment dynamics of important variables like firm value, dividend payout, and investment differs qualitatively depending on whether the reform comes expected or not. We are also able to demonstrate a genuine welfare gain from temporary tax cuts. Impulse responses generated by our numerical method can be retraced by phase diagram analysis which facilitates explanation and interpretation of the produced results.
Keywords: H20; H30; E62; O40; 330; Tax reform; anticipation effects; investment; economic growth; welfare; corporate finance; capital taxation